THE CORRELATION BETWEEN TEACHER’S STRATEGIES AND STUDENTS’ WRITING ABILITY - Andriansyah, Andriansyah (Ar Raniry : International Journal of Islamic Studies, 2017)
The purpose of this research is to identify a correlation between teacher’s strategy and students’ writing ability. Teachers have to modify their strategies in teaching writing related to their students performances, abilities and backgrounds. The first phase of the project involves a screening interview where we identify students’ difficulties in writing. We also use students’ writing products to validate answers on the screening interview. The final phase involves observations and questionnaires where we use several assessments to confirm the student’s diagnosis and examine the connection between their abilities and strategies that teacher used. The result shows that the teacher’s strategies in teaching writing boost students to develop their ideas in writing, especially in enhancing vocabulary and getting better at grammar. Lastly, it is suggested to the teacher to be able to use the strategies in the classroom called cognitive, meta-cognitive, affective and social.